PENERAPAN KEGIATAN BERMAIN PASIR UNTUK MENINGKATKAN KECERDASAN VISUAL SPASIAL ANAK USIA 5-6 TAHUN DI TK AR RAHIM LIMBUNGAN KECAMATAN RUMBAI PEKANBARU - Yaya Murni Dasril Murni Dasril; Daviq Chairilsyah Daviq Chairilsyah; Ria Novianti Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to investigate the implementation of the sand play activities can improve visual spatial intelligence of children aged 5-6 years in kindergarten Ar Rahim Limbungan Rumbai District of Pekanbaru. This research is a classroom action research. The subject of this study is a kindergartner Ar Rahim Limbungan Rumbai Pekanbaru District of the number of children as much as 22 children consisted of 10 men and 12 daughters. Percentage increase in visual-spatial intelligence of children aged 5-6 years by using sand play in kindergarten Ar Rahim Limbungan Pekanbaru District of Rumbai can be seen from the Pre cycle or before the application of the sand play until the second cycle. On the preliminary data obtained score 223 with a percentage of 42.2%. While the value of the first cycle to 56.3%. The next and the second cycle increases with the value of 81.4%. In testing the hypothesis can be seen improvement gained from each cycle. Where an increase in visual-spatial intelligence obtained prior to the first cycle of action to increase by 33.3%. While improving visual-spatial intelligence from cycle I to cycle II of 44.6%, and the overall improvement of visual-spatial intelligence of initial data to the cycle II of 92.8%.Keywords: Play Sand, Visual Spatial Intelligence